Effect of anti-obesity drug on cardiovascular risk factors: a systematic review and meta-analysis of randomized controlled trials. - Yu-Hao Zhou; Xiu-Qiang Ma; Cheng Wu; Jian Lu; Shan-Shan Zhang; Jia Guo; Shun-Quan Wu; Xiao-Fei Ye; Jin-Fang Xu; Jia He (PLoS ONE)
Background Anti-obesity drugs are widely used to prevent the complications of obesity, however, the effects of anti-obesity drugs on cardiovascular risk factors are unclear at the present time. We carried out a comprehensively systematic review and meta-analysis to assess the effects of anti-obesity drugs on cardiovascular risk factors. Methodology and principal findings We systematically searched Medline, EmBase, the Cochrane Central Register of Controlled Trials, reference lists of articles and proceedings of major meetings for relevant literatures. We included randomized placebo-controlled trials that reported the effects of anti-obesity drugs on cardiovascular risk factors compared to placebo. Overall, orlistat produced a reduction of 2.39 kg (95%CI-3.34 to -1.45) for weight, a reduction of 0.27 mmol/L (95%CI: -0.36 to -0.17) for total cholesterol, a reduction of 0.21 mmol/L (95%CI: -0.30 to -0.12) for LDL, a reduction of 0.12 mmol/L (95%CI: -0.20 to -0.04) for fasting glucose, 1.85 mmHg reduction (95%CI: -3.30 to -0.40) for SBP, and a reduction of 1.49 mmHg (95%CI: -2.39 to -0.58) for DBP. Sibutramine only showed effects on weight loss and triglycerides reduction with statistical significances. Rimonabant was associated with statistically significant effects on weight loss, SBP reduction and DBP reduction. No other significantly different effects were identified between anti-obesity therapy and placebo. Conclusion/significance We identified that anti-obesity therapy was associated with a decrease of weight regardless of the type of the drug. Orlistat and rimonabant could lead to an improvement on cardiovascular risk factors. However, Sibutramine may have a direct effect on cardiovascular risk factors.